The Causes of Debris-Covered Glacier Thinning: Evidence for the Importance of Ice Dynamics From Kennicott Glacier, Alaska - Anderson, Leif S.; Armstrong, William H.; Anderson, Robert S.; Scherler, Dirk; Petersen, Eric (Frontiers in Earth Science, 2021)
The cause of debris-covered glacier thinning remains controversial. One hypothesis asserts that melt hotspots (ice cliffs, ponds, or thin debris) increase thinning, while the other posits that declining ice flow leads to dynamic thinning under thick debris. Alaska’s Kennicott Glacier is ideal for testing these hypotheses, as ice cliffs within the debris-covered tongue are abundant and surface velocities decline rapidly downglacier. To explore the cause of patterns in melt hotspots, ice flow, and thinning, we consider their evolution over several decades. We compile a wide range of ice dynamical and mass balance datasets which we cross-correlate and analyze in a step-by-step fashion. We show that an undulating bed that deepens upglacier controls ice flow in the lower 8.5 kilometers of Kennicott Glacier. The imposed velocity pattern strongly affects debris thickness, which in turn leads to annual melt rates that decline towards the terminus. Ice cliff abundance correlates highly with the rate of surface compression, while pond occurrence is strongly negatively correlated with driving stress. A new positive feedback is identified between ice cliffs, streams and surface topography that leads to chaotic topography. As the glacier thinned between 1991 and 2015, surface melt in the study area decreased, despite generally rising air temperatures. Four additional feedbacks relating glacier thinning to melt changes are evident: the debris feedback (negative), the ice cliff feedback (negative), the pond feedback (positive), and the relief feedback (positive). The debris and ice cliff feedbacks, which are tied to the change in surface velocity in time, likely reduced melt rates in time. We show this using a new method to invert for debris thickness change and englacial debris content (~0.017 % by volume) while also revealing that declining speeds and compressive flow led to debris thickening. The expansion of debris on the glacier surface follows changes in flow direction. Ultimately, glacier thinning upvalley from the continuously debris-covered portion of Kennicott Glacier, caused by mass balance changes, led to the reduction of flow into the study area. This caused ice emergence rates to decline rapidly leading to the occurrence of maximum, glacier-wide thinning under thick, insulating debris.